Sistem Rekomendasi Pemilihan Menu Brownies Cinta dengan Metode Content Based Filtering - Fauziah Fanny; Faulinda Ely Nastiti; Rudi Susanto (Universitas Islam Raden Rahmat, Malang, 2024)
Culinary businesses in Indonesia, such as Brownies Cinta Karanganyar, face challenges in helping consumers choose products with the best taste. This study aims to implement a Brownies Cinta menu recommendation system using the Content-Based Filtering method with the cosine similarity algorithm. The system was developed through the SDLC Waterfall stages: planning, design, implementation, testing, and maintenance. The TF-IDF algorithm is used to calculate the initial value, which is then processed with cosine similarity to produce accurate recommendations. The test results show that the